Men's skincare trends: Korean wave hyperreality media men's beauty standards - Novianti, Nadia; Darmawan, Diaz Restu (Universitas Islam Negeri Ar-Raniry, 2024)
The desire for a white and smooth face is not only a woman's need, but has become a man's need as well. This new phenomenon is influenced by the globalization of the Korean wave, which has created contemporary cultural standards. Such as the increased need for facial skin care products among men. Therefore, this paper discusses how the development of the Korean Wave affects men's skincare needs that are provided through Instagram. It even leads to the emergence of a new hyperreality that replaces the previous cultural standard. Hyperreality is the result of postmodernism, which makes the role of media a source of new human needs. The preparation of this paper is through the netnography method and literature review. The netnography method itself is a development of ethnography that uses Internet media to find information and connect with informants. Netnography helps research to examine social phenomena that appear in the Internet world, and has special methods in interviewing and validating information data obtained from Internet media. This paper shows that Somethinc's local product is a symbol of hyperreality that shifts the special needs of one gender to a common need raised by the globalization of the Korean Wave at this time. The new standards of life brought by the media show that the media has penetrated human life. It has even become a new standard or a standard for the continuation of life.